Поетикальні особливості твору Дзвінки Матіяш «Дорога святого якова» - Забаренко, А. Ю.; Шарова, Тетяна Михайлівна; Шарова, Татьяна Михайловна; Sharova, Tetiana (My University, 2021)
UK: У статті розглядаються особливості творчої манери Дзвінки Матіяш. Акцентується увага на поетикальних аспектах у творі письменниці «Дорога Святого Якова». Доведено, що у творі письменниця розкриває власне бачення на життя та оточення, в якому перебуває. EN: The article considers the peculiarities of the creative style of Dzvinka Matiyash. Emphasis is placed on poetic aspects in the work of the writer «The road of Saint Jacob». It is proved that in the work the writer reveals her own vision of life and the environment in which she is.
Poetic Features of the Work by Dzvinka Matiash «The road of Saint Jacob»
Keywords: інклюзія; дорога; художня творчість; свідмість; поетика; inclusion; road; artistic creativity; consciousness; poetics